Computational Approaches on Photon-Attenuation and Coincidence-summing Corrections for the detection of gamma-emitting radionuclides IN foods. (August 2017) - Rolle, Clarence; Lin, Zhichao; Healey, Stephanie
Abstract: Source-based calibration methods used for photon attenuation and coincidence summing corrections are time consuming and require multiple certified standards that match sample geometry with varying densities. Three programs which are capable of simulating a variety of sample geometries, matrix compositions, and sample densities have been examined as alternatives. LabSOCS, ANGLE 3 and GESPECOR are effective at generating efficiency curves for food matrices with a range with different densities. The curves generated have been successfully used to determine activity in food samples. Highlights: Computation of efficiencies by using Monte Carlo methods. Density corrections and coincidence summing can be effectively accounted for. Accurate measurements of radioactive food samples for emergency response scenarios.